Sight and sound out of synch: Fragmentation and renormalisation of audiovisual integration and subjective timing - Freeman, E; Ipser, A; Palmbaha, A; Paunoiu, D; Brown, P; Lambert, C; Leff, A; Driver, J (2013)
The sight and sound of a person speaking or a ball bouncing may seem simultaneous, but their corresponding neural signals are spread out over time as they arrive at different multisensory brain sites. How subjective timing relates to such neural timing remains a fundamental neuroscientific and philosophical puzzle. A dominant assumption is that temporal coherence is achieved by sensory resynchronisation or recalibration across asynchronous brain events. This assumption is easily confirmed by estimating subjective audiovisual timing for groups of subjects, which is on average similar across different measures and stimuli, and approximately veridical. But few studies have examined normal and pathological individual differences in such measures. Case PH, with lesions in pons and basal ganglia, hears people speak before seeing their lips move. Temporal order judgements (TOJs) confirmed this: voices had to lag lip-movements (by ~200msec) to seem synchronous to PH. Curiously, voices had to lead lips (also by ~200msec) to maximise the McGurk illusion (a measure of audiovisual speech integration). On average across these measures, PH's timing was therefore still veridical. Age-matched control participants showed similar discrepancies. Indeed, normal individual differences in TOJ and McGurk timing correlated negatively: subjects needing an auditory lag for subjective simultaneity needed an auditory lead for maximal McGurk, and vice versa. This generalised to the Stream-Bounce illusion. Such surprising antagonism seems opposed to good sensory resynchronisation, yet average timing across tasks was still near-veridical. Our findings reveal remarkable disunity of audiovisual timing within and between subjects. To explain this we propose that the timing of audiovisual signals within different brain mechanisms is perceived relative to the average timing across mechanisms. Such renormalisation fully explains the curious antagonistic relationship between disparate timing estimates in PH and healthy participants, and how they can still perceive the timing of external events correctly, on average. © 2013 Elsevier Ltd.